Activity-Based Costing untuk Efisiensi Belanja: Analisis Standar Biaya Digitalisasi Dokumen Perpajakan pada Direktorat Jenderal Pajak - Nengah Renny Larasati Dewi; Nanda Ayu Wijayanti (Owner : Riset dan Jurnal Akuntansi, 2025)
In the concept of performance-based budgeting, the determination of standard cost is an instrument used in maintaining the efficiency of the government budget. This research aims to estimate the standard cost of tax documents digitalization using the activity-based costing method in government organization. This research also outlines the steps taken in order to implement activity-based costing. This research uses a descriptive quantitative approach in the form of a case study conducted at the Directorate General of Taxes, Ministry of Finance. The research was carried out by document analysis to identify activities, allocate costs to each relevant activity, calculate activity rates, calculate activity costs for products based on the results of document analysis, and confirm through interviews with respondents. The research results show that the estimation of output standard costs for tax document digitalization can be calculated using the activity-based costing method Based on this research, it is known that recording activities consume the most significant costs in producing digital data. The contribution of this research can be used as material in decision making and analysis of the preparation of standards cost in order to achieve budget efficiency in government organization. To enable the implementation of this method government organization, more research in the government sector is needed in the future.